2019
DOI: 10.2478/folmed-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Thyroid Disorders

Abstract: Background: Thyroid diseases are the most common endocrine pathologies second to diabetes. They have been shown to have high genetic impact, and variants in any of the genes involved in the metabolism of thyroid hormones have marked influence on the development of these diseases. Aim: To identify the genes that have been most involved in the development of thyroid pathologies by reviewing the literature with recent relevant articles. Materials and methods: We performed a literature search on the NCBI (National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Other studies have not demonstrated a significant influence of variation in the gene for this enzyme on T4 requirement in hypothyroid patients [48], or on patient-reported outcomes on (or preference for) treatment with LT4 + T3 combination therapy [49]. Further research will be needed to confirm whether genetic variations in deiodinases, and indeed in other sites of cellular access or action of thyroid hormones (such as membrane transporters, nuclear receptors and other sites) may facilitate individualised treatment of hypothyroid patients in the future [44,[50][51][52].…”
Section: Possible Explanations For Continuing Symptoms Despite 'Adequmentioning
confidence: 99%
“…Other studies have not demonstrated a significant influence of variation in the gene for this enzyme on T4 requirement in hypothyroid patients [48], or on patient-reported outcomes on (or preference for) treatment with LT4 + T3 combination therapy [49]. Further research will be needed to confirm whether genetic variations in deiodinases, and indeed in other sites of cellular access or action of thyroid hormones (such as membrane transporters, nuclear receptors and other sites) may facilitate individualised treatment of hypothyroid patients in the future [44,[50][51][52].…”
Section: Possible Explanations For Continuing Symptoms Despite 'Adequmentioning
confidence: 99%
“…Loss-of-function mutations in NF1 lead to uncontrollable activation of kinase and tumorigenesis. Also, the RET protooncogene encodes a receptor tyrosine kinase that mediates extracellular neurotropic signaling to intracellular transduction pathways including the MAPK/ERK pathway ( 24 ). We think that these two diseases occurred coincidentally, because MTC in our patient does not have a common etiological pathway with the NF1, according to the evidence concerning both the NF1 gene and the RET oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…First, the incidences of hyperthyroidism are higher in those with a positive family history [3-5], and genetic background is certainly one of the biggest contributing factors of this family aggregation phenomenon. Second, previous candidate genetic association studies and genome-wide association studies have also identified many predisposing loci of hyperthyroidism in different ethnic groups [6-8]. Nevertheless, most genetic contributing factors for hyperthyroidism are still unexplored and thus require intensive explorations and analyses.…”
Section: Introductionmentioning
confidence: 99%